Structure and Long-Term Stability of Alkylphosphonic Acid Monolayers on SS316L Stainless Steel - Kosian, Medea (Langmuir : the ACS journal of surfaces and colloids, 2016)
Surface modification of stainless steel (SS316L) to improve surface properties or durability is an important avenue of research, as SS316L is widely used in industry and science. We studied, therefore, the formation and stability of a series of organic monolayers on SS316L under industrially relevant conditions. These included acidic (pH 3), basic (pH 11), neutral (Milli-Q water), and physiological conditions [10 mM phosphate-buffered saline (PBS)], as well as dry heating (120 °C). SS316L was modified with alkylphosphonic acids of chain length (CH2)n with n varying between 3 and 18. While alkylphosphonic acids of all chain lengths formed self-assembled monolayers with hydrophobic properties, only monolayers of chain lengths 12-18 formed ordered monolayers, as evidenced by static water contact angle (SCA), X-ray photoelectron spectroscopy (XPS), atomic force microscopy (AFM), and infrared reflection absorption spectroscopy (IRRAS). A long-term stability study revealed the excellent stability of monolayers with chain lengths 12-18 for up to 30 days in acid, neutral, and physiological solutions, and for up to 7 days under dry heating. Under strong basic conditions a partial breakdown of the monolayer was observed, especially for the shorter chain lengths. Finally, the effect of multivalent surface attachment on monolayer stability was explored by means of a series of divalent bisphosphonic acids